Analisis Respon Peserta Didik Terhadap Penggunaan Media Flash Card Berbasis Augmented Reality Pada Pembelajaran Geografi Materi Siklus Hidrologi Kelas X Di SMA Negeri 1 Paguyaman Pantai - Kuuna, Wahyudin; Yusuf, Daud; Masruroh, Masruroh (-, 2026)
The development of digital technology in education encourages innovation in learning media, particularly in Geography, which contains abstract concepts such as the hydrological cycle. This material requires clear visualization to be easily understood by students. Therefore, the use of Augmented Reality–based learning media combined with flash cards is a relevant alternative to create more interactive and engaging learning experiences. This study aims to analyze students’ responses to the use of Augmented Reality–based flash card media in Geography learning on hydrological cycle material. The study employed a descriptive quantitative method, with data collected through questionnaires distributed to 15 tenth-grade students at SMA Negeri 1 Paguyaman Pantai. The results showed that the Augmented Reality–based flash card media obtained an average percentage score of 83.4%, categorized as very feasible. In terms of assessment aspects, the media appearance aspect achieved a score of 85.8%, ease of use reached 81.3%, while the learning benefits aspect obtained a score of 82.2%, categorized as feasible. The media was considered capable of presenting material visually and interactively and was easy to operate, thereby increasing students’ interest, attention, and active engagement. These findings indicate that Augmented Reality–based flash card media is feasible for use and has strong potential for further development to support Geography learning.